The blood pressure effect and related plasma levels of flavan-3-ols in spontaneously hypertensive rats. Issue 11 (21st August 2015) - Quiñones, Mar; Margalef, Maria; Arola-Arnal, Anna; Muguerza, Begoña; Miguel, Marta; Aleixandre, Amaya
Abstract : We studied the short-term antihypertensive effect of flavan-3-ols (−)-epicatechin, (+)-catechin and (−)-catechin, in spontaneously hypertensive rats (SHR). Abstract : We studied the short-term antihypertensive effect of flavan-3-ols (−)-epicatechin, (+)-catechin and (−)-catechin, in spontaneously hypertensive rats (SHR). Plasma metabolites and the corresponding plasma antioxidant capacity were determined. All the assayed flavan-3-ols decreased systolic blood pressure (SBP) in SHR. Their antihypertensive effects were less pronounced than that of Captopril (50 mg kg −1 ) and were not shown in normotensive Wistar-Kyoto rats. 6 mg kg −1 (−)-epicatechin caused the maximum decrease in SBP. The maximum effects of the catechin monomers were observed post-administration of 0.5 mg kg −1 of flavan-3-ols, (−)-catechin being the least effective among the three assayed compounds. Glucuronide and methyl glucuronide metabolites were obtained in the flavan-3-ol treated SHR, but it was not possible to relate the antihypertensive effect of the assayed flavan-3-ols with a concrete plasma metabolite or with their antioxidant effect. In conclusion, the studied flavan-3-ols could be responsible for the antihypertensive effect of cocoa products.